Efficacy and Safety of Mitomycin Gel (UGN-101) as an Adjuvant Therapy After Complete Endoscopic Management of Upper Tract Urothelial Carcinoma. Issue 5 (19th May 2023) - Labbate, Craig; Woldu, Solomon; Murray, Katie; Rose, Kyle; Sexton, Wade; Tachibana, Isamu; Kaimakliotis, Hristov; Jacob, Joseph; Dickstein, Rian; Linehan, Jennifer; Nieder, Alan; Bjurlin, Marc; et al.
Abstract : Purpose: We describe a novel application of the reverse thermal polymer gel of mitomycin C (UGN-101) as adjuvant therapy after complete endoscopic ablation of upper tract urothelial carcinoma. Materials and Methods: We retrospectively reviewed patients treated with UGN-101 from 15 high-volume centers. Adjuvant therapy was defined as treatment administered following visually complete endoscopic ablation. Response at primary endoscopic evaluation was defined as no visual tumor or negative biopsy. Ipsilateral disease-free and progression-free survival were estimated by the Kaplan-Meier method. Ureteral stenosis and other adverse events were abstracted from the medical records. Ureteral stenosis was defined as a condition requiring ureteral stent or nephrostomy, or that would typically warrant stent or nephrostomy. Results: Adjuvant UGN-101 after complete endoscopic ablation was used in 52 of 115 (45%) renal units in the oncologic analysis. At first endoscopic evaluation, 36/52 (69%) were without visible disease. At 6.8 months' median follow-up, the ipsilateral disease-free rate was 63%. Recurrence after adjuvant UGN-101 therapy was more likely in multifocal tumors compared to unifocal (HR 3.3, 95% CI 1.07-9.91). Compared with UGN-101 treatment for chemoablation of measurable disease, there were significantly fewer disease detections with adjuvant therapy ( P < .001). Ureteral stenosis after UGN-101 was diagnosed in 10 patients (19%) undergoing adjuvant therapy compared to 17 (29%) undergoing chemoablative therapy ( P = .28). Conclusions: In patients being considered for UGN-101, maximal endoscopic ablation prior to UGN-101 treatment may result in fewer patients with disease at first endoscopy and possibly fewer adverse events than primary chemoablative therapy. Longer follow-up is needed to determine if UGN-101 after complete endoscopic ablation will lead to durable disease-free interval.